Ruptured abdominal aorta aneurysms.: Análisis de una serie de 18 casos - Lucinschi, Alicia; Matteucci, Pablo; Mazza, Norma (Cirugía del Uruguay, 1987)
A small serie of 19 cases of ruptured abdominal aortic aneurysms assisted in an ICU facility is presented. The mean age was 69 y.o. and all the patients have had previous important cardiac and respiratory diseas.es. There were 10 perioperative deaths due to multisystemic failures